O pewnym podejściu do kategoryzacji aspektualności leksykalnej w języku rosyjskim - Klimonov, Vladimir (Studia Rossica Posnaniensia, 2017)
The paper deals with the categorization of verbal situations (lexical aspects: events, processes, and states) and their subcategorization according to finer Aktionsart distinctions. The proposed two-component model for the categorization of lexical aspectuality is based on uniform quantitative features. Four subclasses of events will be distinguished, which will be subclassified further.